2021
DOI: 10.34117/bjdv7n9-573
|View full text |Cite
|
Sign up to set email alerts
|

Danos causados ao meio ambiente, animais e ao homem com a utilização de agrotóxico: revisão bibliográfica / Damage caused environment, animals and man with the use pesticides: bibliographic review

Abstract: porém, acontecia o desequilíbrio ambiental como: de a contaminação de solo, rios, meio ambiente e de pessoas que sofrem com doenças causadas por agrotóxicos. Portanto, o objetivo do presente trabalho foi analisar os danos causados ao meio ambiente, animais e ao homem com a utilização de agrotóxico. Assim sendo, os produtos agrícolas têm uma grande importância para a produção nas plantações, e para gerar lucro aos produtores, mas sabemos que mesmo sendo eficientes no controle de pragas, esses produtos causam da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…In 2015, Brazil sprayed approximately 899 million liters of pesticides, with soy, corn, and sugar cane accounting for 82% of the entire volume used in the country (Pignati et al, 2017). The use of chemical products guarantees protection to the means of production, but with the consumption of approximately 1 million tons per year it causes damage to man and the environment, such as diseases to human health and destruction of soils and rivers (Demartelaere et al, 2021). Vendramim & Castiglioni (2000) reported that the use of toxic compounds of vegetable origin is not a recent technique since their use in pest control was common in tropical countries before the advent of synthetic insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Brazil sprayed approximately 899 million liters of pesticides, with soy, corn, and sugar cane accounting for 82% of the entire volume used in the country (Pignati et al, 2017). The use of chemical products guarantees protection to the means of production, but with the consumption of approximately 1 million tons per year it causes damage to man and the environment, such as diseases to human health and destruction of soils and rivers (Demartelaere et al, 2021). Vendramim & Castiglioni (2000) reported that the use of toxic compounds of vegetable origin is not a recent technique since their use in pest control was common in tropical countries before the advent of synthetic insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Porém, o controle químico de insetos, pragas e doenças possui custo elevado e causa impactos negativos ao ambiente e aos seres humanos (DEMARTELAERE et al, 2021). Por isto, nos últimos anos percebe-se o aumento da preocupação da sociedade com aspectos relacionados à poluição, preservação e recuperação ambiental, e com a contaminação dos alimentos.…”
unclassified